Nutritional Status and Physical Fitness of Full Day Elementary School Students (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Nutritional status can be measured through the adequacy of nutrients obtained from food which are digested every day. The increasing number of healthy food absorbed by the body can increase the physical fitness of the body.Â The purpose of this research was to do counseling in order to understand the nutritional status and physical fitness level of fifth grade student at Tunas Harapan Islamic Elementary School in Sendangmulyo, Tembalang, Semarang. The physical fitness level was measured using nutritional status and physical fitness test (TKJI). The data were obtained using descriptive method with measurement and test techniques. These data were obtained from measurement of height, weight, age, and physical fitness tests (TKJI). This study found that the nutritional status of fifth grade students in Tunas Harapan Islamic Elementary School were included in normal nutrition category and moderate physical fitness level.